Microwave Assisted Pyrolysis of Plastic Waste. (2016) - Aishwarya, K.N.; Sindhu, Nangarthody
Abstract: Plastic waste is recognized to have pertinent disposal or reprocessing problems under environmental and economic sustainable conditions. These developments may be a challenge for industrial and academic research. In this context pyrolysis represent a modern, effective alternative to undergo treatment of waste as long as it has the potential to generate value-added products. Anyway enhancements in the heat transfer technology are vital to optimize the efficiency of the process itself. This work prominences on the use of microwave irradiation as one of the most gifted heating technologies for pyrolysis, due to its ability to heat quickly and directly any microwave absorbing material. A microwave reactor was designed and fabricated using a microwave oven operating at a frequency of 2.45GHz with a variable energy output up to 5kW, quartz reactor, condensers and cold trap; this made the design appealing for any future industrial-sized microwave reactor. The optimal pyrolysis working condition led to the production of a suitable product for a fuel application. A mixture of various types of plastics is taken as samples. Carbon was used as the microwave absorbent. The pyrolyzed products (oils/waxes) were analyzed using various techniques like GCMS, FTIR and TGA. The char obtained after pyrolysis is characterized using techniques like SEM and XRD.